Reassortment of newly emergent clade 2.3.4.4b A(H5N1) highly pathogenic avian influenza A viruses in Bangladesh - Subrata Barman; Jasmine C. M. Turner; M. Kamrul Hasan; Sharmin Akhtar; Trushar Jeevan; John Franks; David Walker; Nabanita Mukherjee; Patrick Seiler; Lisa Kercher; Pamela McKenzie; Robert G. Webster; et al. (Emerging Microbes and Infections)
Avian influenza active surveillance was conducted in Bangladesh from January 2022 to November 2023 in live-poultry markets (LPMs) and Tanguar Haor wetlands. The predominant viruses circulating in LPMs were low pathogenic avian influenza (LPAI) A(H9N2) and clade 2.3.2.1a highly pathogenic avian influenza (HPAI) A(H5N1) viruses. Non-H9N2 LPAIs were found at Tanguar Haor and at a lower prevalence in LPMs. Starting from June 2023, we detected novel genotypes of clade 2.3.4.4b A(H5N1) viruses from ducks in LPMs. The HA, NA, and M genes of these viruses are related to those of 2020 European clade 2.3.4.4b H5N1 viruses such as A/Eurasian Wigeon/Netherlands/1/2020 (Netherlands/1). However, analyses of the other five gene segments’ sequences identified three distinct genotypes (BD-G2, BD-G3, and BD-G4). BD-G2 viruses were closely related to the clade 2.3.4.4b H5N1 viruses that have been detected in Japan and nearby regions since November 2022. BD-G3 viruses were reassortants, with gene segments from other Eurasian LPAI viruses. BD-G4 viruses were similar to BD-G2 viruses, but their NS gene was accrued from contemporary Bangladeshi clade 2.3.2.1a A(H5N1) viruses. The ability of any of the clade 2.3.4.4b viruses to displace the long-entrenched 2.3.2.1a A(H5N1) viruses in Bangladesh is unknown.